2004
DOI: 10.1002/adma.200306459
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes with Graphitic Wings

Abstract: Graphitic platelets (wings) on carbon nanotubes are produced using a new two‐step chemical vapor deposition method (see Figure and inside cover). Chemical attack during the process, aided by curvature‐induced strain, rips open the outer nanotube walls and produces an irregular and corrugated surface. The new morphology, which presents a highly modulated and active nanotube surface, could facilitate posterior functionalization or direct composite fabrication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
3
19
0
Order By: Relevance
“…The rolling mechanism is similar to that reported by Chen et al [25] and Trasobares et al [26] where rolling of vanadate layers and 'wings' are observed in each respective case. The growth direction of the hollow-axis of the nanotubes is radially toward the core of the structure.…”
Section: Growth Stages Of the Nanourchinsupporting
confidence: 88%
“…The rolling mechanism is similar to that reported by Chen et al [25] and Trasobares et al [26] where rolling of vanadate layers and 'wings' are observed in each respective case. The growth direction of the hollow-axis of the nanotubes is radially toward the core of the structure.…”
Section: Growth Stages Of the Nanourchinsupporting
confidence: 88%
“…Interestingly, in previous work we demonstrated that the same hydrogen-poor plasmas can still selectively etch the sidewalls of the horizontally oriented MWCNTs under an Ar-rich Ar/CH 4 discharge, leading to the growth of graphitic structures on the sidewalls. [27] Since the process parameters for growing both nanocarbon materials are the same in the Ar/CH 4 plasma, the key factor determining the resultant nanostructure is the initial nucleation sites. Our ongoing work is aimed at fabricating periodic arrays of UNCD and CNTs by patterning nanodiamond and catalyst particles with the aid of lithographic techniques such as electron-beam lithography.…”
mentioning
confidence: 99%
“…4(b) and (c). On the other hand, the high temperature is also one of the important factors for forming graphitic nanosheets since carbon nanomaterials prefer to form amorphous structure at low temperature [10]. Moreover, the hydrogen in the plasma is also critical for forming nanosheets.…”
Section: Resultsmentioning
confidence: 99%
“…One way to solve these problems is to grow the thick CNTs as supports [8,9]. The other way is to prepare the winglike CNTs [10,11]. However, up to date, the FEE properties of the wing-like CNTs have not been investigated, and the mechanism underlying the enhancement of FEE properties in the tree-and wing-like CNTs is unclear.…”
Section: Introductionmentioning
confidence: 96%